ASSL: A Software Engineering Approach to Autonomic Computing. - Vassev, Emil; Hinchey, Mike (Computer (00189162), 2009)
The article offers information on Automatic System Specification Language (ASSL), a software technology dedicated to reducing the complexity of automatic computing (AC) by making existing complex systems autonomic. ASSL exhibits self-management of complex system that provides a framework for formal specification, validation and code generation of autonomic systems (AS). Information is also provided on how ASSL could provide a toolset that software developers can use to edit and validate ASSL specifications and generate Java code.